2022
DOI: 10.3390/ijerph19042316
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene Practices and Knowledge among Adolescents Aged between 15 and 17 Years Old during Fixed Orthodontic Treatment: Multicentre Study Conducted in France

Abstract: The aims of this study were to assess oral health knowledge, attitudes, and practices among orthodontic patients between the ages of 15 and 17 years old compared to adolescents without orthodontic treatment. This cross-sectional study included 392 adolescents drawn from various French teaching hospitals. A closed-ended questionnaire was used to collect data. Adolescents undergoing orthodontic treatment had a higher knowledge of oral health than adolescents without orthodontic treatment. The majority of adolesc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…Ericsson et al (2012) [ 15 ] stated that 76% of adolescents brushed their teeth at least two times a day, with only 4% of the sample flossing every day. In a study conducted by Inquimbert et al [ 19 ], the majority (69%) of adolescents declared brushing their teeth twice a day, with a higher frequency found in the subjects undergoing orthodontic treatment. Interdental flossing was still performed more often in the latter group compared to others (35.1% vs. 4.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ericsson et al (2012) [ 15 ] stated that 76% of adolescents brushed their teeth at least two times a day, with only 4% of the sample flossing every day. In a study conducted by Inquimbert et al [ 19 ], the majority (69%) of adolescents declared brushing their teeth twice a day, with a higher frequency found in the subjects undergoing orthodontic treatment. Interdental flossing was still performed more often in the latter group compared to others (35.1% vs. 4.4%).…”
Section: Discussionmentioning
confidence: 99%
“…That said, the proportion of adolescents routinely using dental floss was still very low: only 10% of girls wearing braces were flossing regularly. Greater attention to oral hygiene procedures was found among adolescents that undergo orthodontic treatments compared to their counterparts [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining good oral health self-management ability in children with fixed orthodontics during treatment is the key to maintaining periodontal health, preventing plaque formation, and improving oral health and quality of life. Research on oral health self-management of children with fixed orthodontics has generally increased in recent years, and related interventions have emerged one after another [ 8 , 9 ] However, it was found that most children with fixed orthodontics could not carry out adequate oral health self-management, which may invariably affect the continuous self-management process of patients throughout the orthodontic treatment [ 10 ]. Most studies on oral health self-management of adolescent orthodontic patients are quantitative in china.…”
Section: Introductionmentioning
confidence: 99%
“…In this particular context, some factors may cause changes in the response of the periodontium in an attempt to maintain gingival health [ 16 ]. All of these predisposing factors increase the risk of dental lesions and early inflammatory gingival disease in adolescents [ 14 , 17 , 18 ], and the most common method of controlling oral hygiene is tooth brushing, i.e., individual oral prophylaxis with interdental brushes for adolescents with fixed orthodontic treatment [ 19 ], and local fluorization. However, the efficiency of toothbrushing is influenced by certain factors such as the brushing technique, the frequency and duration of brushing, the type and shape of the toothbrush and the type of toothpaste used [ 20 ].…”
Section: Introductionmentioning
confidence: 99%